1986
DOI: 10.1029/gl013i009p00905
|View full text |Cite
|
Sign up to set email alerts
|

Harmonically structured ULF pulsations observed by the AMPTE CCE Magnetic Field Experiment

Abstract: Spectrograms of ULF waves in the 0 to 80 mHz frequency range have been prepared from magnetic field data obtained by the elliptically orbiting AMPTE/CCE satellite (with an apogee of approximately 8.8 Re). The most prominent feature of these spectrograms (which cover a full 15.6 hour orbit) is the presence of harmonically structured, azimuthally polarized pulsations in the outer magnetosphere during daytime hours. The frequencies of these pulsations decrease with increasing radial distance from the earth, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
100
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(121 citation statements)
references
References 21 publications
18
100
1
2
Order By: Relevance
“…Singer and Kivelson, 1979;Singer et al, 1982;Engebretson and Cahill, 1981;Engebretson et al, 1986). However, single spacecraft observations have a limitation as they exhibit an ambiguity between spatial and temporal variations.…”
Section: Introductionmentioning
confidence: 99%
“…Singer and Kivelson, 1979;Singer et al, 1982;Engebretson and Cahill, 1981;Engebretson et al, 1986). However, single spacecraft observations have a limitation as they exhibit an ambiguity between spatial and temporal variations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous spectral analyses of the same data set had indicated that discrete-frequency compressional pulsations are not evident in the satellite data (Engebretson et al, 1986). In the new study, Anderson and Engebretson (1995) con®rm the absence of discrete compressional oscillations, but they also ®nd high positive correlation between the amplitudes of the toroidal and compressional components.…”
Section: Pc 3±4 Wavesmentioning
confidence: 52%
“…Yumoto (1985) used ISEE 3 (International Sun/Earth Explorer) and GOES 2 (Geostationary Operational Environmental Satellites) observations and measurements from two ground stations to relate solar wind data to Pc3s on the ground and suggested that compressional waves from a broadband source near the magnetopause couples to FLRs near the Earth. Engebretson et al (1986) cited the same mechanism to explain simultaneous observations of multiple harmonics of toroidal mode FLR's and an increase in broadband compressional wave power. Heilig et al (2007) computed the latitudinal distribution of dayside Pc3 amplitudes and concluded that UWs enter near the subsolar point as compressional waves where they couple to the Alfvén mode resulting in field line oscillations.…”
Section: P R Sutcliffe Et Al: Spectral Structure Of Pc3-4 Pulsatiomentioning
confidence: 99%
“…Yumoto et al, 1984;Le and Russell, 1992). Engebretson et al (1986) noted the IMF control of Pc3-4 pulsations when activity at low L shells (L ∼ 3) suddenly resumed upon IMF orientation changing from quasi-perpendicular (large cone angle) to quasi-parallel (small cone angle). Heilig et al (2010) showed that the intensity of UW-related Pc3s is dependent on the density of the solar wind, and density-related parameters like the dynamic pressure and distance from the magnetopause to the Earth.…”
Section: P R Sutcliffe Et Al: Spectral Structure Of Pc3-4 Pulsatiomentioning
confidence: 99%
See 1 more Smart Citation